Waste Management in Malalayang District, Manado City - Tambun, Edgard; Masengi, Evi; Mokat, Jetty E.H. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to explain how waste handling in Malalayang Sub-district, Manado City. This research uses descriptive qualitative research methods and seeks the necessary data by means of observation, interviews and document studies in the Manado City Sub-district. The results of the study found that the waste management planning carried out by Malalayang sub-district was not maximized.  This can be seen from the absence of law enforcement against transportation that dumps garbage in Malalayang Subdistrict, besides that there is no planned and measurable waste handling procedure, because so far it is only to complete administratively but in its implementation in the field it is not done.